Translated Literature in Contemporary Slovenia - Blatnik, Andrej (Knygotyra, 2020)
Based on a typological model borrowed from sociology, this article analyzes literary translation support mechanisms in the world and especially in Slovenia. It tracks the growing inclusion of translation policies in the national cultural policies and subsequent growth of the translated books in the book subsidy system and their strong presence in the reading field. With the help of statistical data it shows the status of translated literature in Slovenian reading habits.
Keywords: translating; cultural policies; reading field